Catabolite control protein C contributes to virulence and hydrogen peroxide-induced oxidative stress responses in Listeria monocytogenes - Ogunleye, Seto C.; Islam, Shamima; Chowdhury, Q. M. Monzur Kader; Ozdemir, Ozan; Lawrence, Mark L.; Abdelhamed, Hossam (Frontiers in Microbiology, 2024)
Listeria monocytogenes causes listeriosis, an infectious and potentially fatal disease of animals and humans. A diverse network of transcriptional regulators, including LysR-type catabolite control protein C (CcpC), is critical for the survival of L. monocytogenes and its ability to transition into the host environment. In this study, we explored the physiological and genetic consequences of deleting ccpC and the effects of such deletion on the ability of L. monocytogenes to cause disease. We found that ccpC deletion did not impact hemolytic activity, whereas it resulted in significant reductions in phospholipase activities. Western blotting revealed that the ΔccpC strain produced significantly reduced levels of the cholesterol-dependent cytolysin LLO relative to the wildtype F2365 strain. However, the ΔccpC mutant displayed no significant intracellular growth defect in macrophages. Furthermore, ΔccpC strain exhibited reduction in plaque numbers in fibroblasts compared to F2365, but plaque size was not significantly affected by ccpC deletion.In a murine model system, the ΔccpC strain exhibited a significantly reduced bacterial burden in the liver and spleen compared to the wildtype F2365 strain. Interestingly, the deletion of this gene also enhanced the survival of L. monocytogenes under conditions of H2O2-induced oxidative stress.Transcriptomic analyses performed under H2O2-induced oxidative stress conditions revealed that DNA repair, cellular responses to DNA damage and stress, metalloregulatory proteins, and genes involved in the biosynthesis of peptidoglycan and teichoic acids were significantly induced in the ccpC deletion strain relative to F2365. In contrast, genes encoding internalin, 1-phosphatidylinositol phosphodiesterase, and genes associated with sugar-specific phosphotransferase system components, porphyrin, branched-chain amino acids, and pentose phosphate pathway were significantly downregulated in the ccpC deletion strain relative to F2365. This finding highlights CcpC as a key factor that regulates L. monocytogenes physiology and responses to oxidative stress by controlling the expression of important metabolic pathways.